Aza-Based Donor-Acceptor Conjugated Polymer Nanoparticles for Near-Infrared Modulated Photothermal Conversion - Zhang, Guobing; Ma, Suxiang; Wang, Weiwei; Zhao, Yao; Ruan, Jiufu; Tang, Longxiang; Lu, Hongbo; Qiu, Longzhen; Ding, Yunsheng (Frontiers in Chemistry, 2019)
It is highly desired that synthesis of photothermal agents with near-infrared (NIR) absorption, excellent photostability, and high photothermal conversion efficiency are essential for potential applications. In this work, three (D-A) conjugated polymers (PBABDF-BDTT, PBABDF-BT, and PBABDF-TVT) based on aza-heterocycle, bis(2-oxo-7-azaindolin-3-ylidene)benzodifurandione (BABDF) as the strong acceptor, and benzodithiophene-thiophene (BDTT), bithiophene (BT), and thiophene-vinylene-thiophene (TVT) as the donors, were designed and synthesized. The conjugated polymers showed significant absorption in the NIR region and a maximum absorption peak at 808 nm by adjusting the donor and acceptor units. Their photothermal properties were also investigated by using poly(ethylene glycol)-block-poly(hexyl ethylene phosphate) (mPEG-b-PHEP) to stabilize the conjugated polymers. Photoexcited conjugated polymer (PBABDF-TVT) nanoparticles underwent non-radiative decay when subjected to single-wavelength NIR light irradiation, leading to an excellent photothermal conversion efficiency of 40.7%. This work indicated the aza-heterocycle BABDF can be a useful building block for constructing D-A conjugated polymer with high conversion efficiency.